(3Sde GdefGQI aj ebheGJ (B( (3GdchGcH (B) (3GdSjGQIs - (3TeS GdOjf eMeO Hf CHi GdaJM GdUhai GdTGaYj Gdahi GdeUQjs; (3GdUhaj , eMeO Hf CHj GdaJM Gdahj GdeUQj, TeS GdOjf,J (B853 (3g` s
(3ChdgG (B:s
(3hHYO , agPG LOGhd edNUI ef GdcJH GdeWhdI SejJgG HSde GdefGQI ai ebheGJ (B( (3GdchGcH (B) (3GdSjGQI EPG CQOJ ebhe GdTeS aGLeY hSWgG hNGUJgG s
(3BNQgG (B:s
(3JeJ GdQSGdI HMeO Gddg s
(3HChdgG Jedc eDQN SfI (B1164(3g`s
(3GdeNWhWI ai ebOeI ef UaMI hGMOI hGdHbjI ai LOGhds
(3HBNQgG edGMXGJ hJhVjMGJ JJUd HehVhY GdQSGdIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B326 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B117s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B159 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
Keywords: (3Gdadcs